Libel And Its Relation To Freedom Of Speech: A Comparative Study Between Malaysian Laws And The Islamic Legal Principles - Hasbollah Bin Mat Saad (Universiti Sains Islam Malaysia, 2024)
Matric : 3120042(FSU)